2009
DOI: 10.1017/s0007114509992297
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and home environmental predictors of change in sugar-sweetened beverage consumption among adolescents

Abstract: beverage (SSB) consumption may increase risk for unnecessary weight gain. To develop interventions discouraging consumption, more insight is needed about cognitive and environmental predictors related to the decrease in SSB consumption. The present paper aims (1) to describe the relationship between potential cognitive determinants of change (attitudes, subjective norms, perceived behavioural control and intentions) and perceived environmental factors (family food rule and home availability of SSB) with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 29 publications
8
73
3
Order By: Relevance
“…Such findings add to previous research highlighting the important role of food availability within the home (24,50) . It has long been known from behaviour modification studies that environmental manipulation, such as food visibility and availability, can have potent effects on behaviour (51) .…”
Section: Discussionsupporting
confidence: 77%
“…Such findings add to previous research highlighting the important role of food availability within the home (24,50) . It has long been known from behaviour modification studies that environmental manipulation, such as food visibility and availability, can have potent effects on behaviour (51) .…”
Section: Discussionsupporting
confidence: 77%
“…Although limited information exists on whether attitudes about substance use and soda intake cluster in families, recent research has shown that parents and peers influence adolescent substance use 36 as well as calorically sweetened beverage intake. 37,38 Adolescents whose parents have favorable attitudes for alcohol, tobacco, and other drug uses or adolescents whose friends use drugs are more likely to be involved in substance use. 36 In addition, adolescents without restrictive family food rules (ie, always allowed to drink calorically sweetened beverages) 38 or youth with misperceptions (mostly overestimation) of peer calorically sweetened beverage intakes are more likely to consume calorically sweetened beverages.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Adolescents whose parents have favorable attitudes for alcohol, tobacco, and other drug uses or adolescents whose friends use drugs are more likely to be involved in substance use. 36 In addition, adolescents without restrictive family food rules (ie, always allowed to drink calorically sweetened beverages) 38 or youth with misperceptions (mostly overestimation) of peer calorically sweetened beverage intakes are more likely to consume calorically sweetened beverages. 37 We were not able to find any published studies examining possible associations between being victimized and calorically sweetened beverage intake.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size varied from 100 [36] to 2746 [37]. The majority of the studies were conducted in the USA (5/17) [36,44,45,47,49] followed by The Netherlands (4/17) [39,41,43,48], representing 52.9% of the total. Other countries represented in the descriptive synthesis were in Norway [40,46], Sweden [50,52], Australia [51], Canada [38], and New Zealand [42].…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…Of the 17 studies, the majority (52.9%) examined sugar sweetened beverages intake (e.g., artificial juices-powder and nectar, sport energy drinks, soft drinks, and flavored milk) [36,37,39,[41][42][43][44]48], followed by fruit and vegetables intake (47.1%) (i.e., fresh, frozen, and/or canned) [37,38,42,45,47,49,50], four examined the consumption of sugar, fat, and/or sodium-rich snacks (e.g., cookies, fish and chips* [typical dish from Australia, New Zealand, and the UK], fried chicken, fried snacks [i.e., nuts, corn, and potato chips], pastries [e.g., tarts, baked snacks, cakes], hamburgers, pizza, sweets, and candies) [37,42,47,51], and only two (11.1%) examined breakfast items food intake (i.e., milk and bread [e.g., skim-, low-medium-, and full-fat milk, and highfiber bread]) [40,46]. It is important to highlight that four studies divided the food/beverages items into two categories: healthy/core foods and unhealthy/non-core foods [37,42,45,51].…”
Section: Food Consumption Assessmentmentioning
confidence: 99%